Fontes de resistência à traça-da-castanha em cajueiro-anão - Duarte, Poliana Martins (2018)
Throughout its development, the dwarf cashew is attacked by several pests, especially the moth (Anacampis phytomiella), a key pest of true fruits (cashew nuts). The losses caused by chemical control, currently the only method used to manage this species, reveal the need to develop sustainable control methods such as plant resistance to insects. This can be expressed by morphological and chemical characteristics unfavorable to the phytophagous insect. The identification of these characteristics may contribute to the selection of genotypes resistant to insect pests in breeding programs. In this work, the objective was (1) to determine the resistance levels of 13 genotypes of dwarf cashew nuts; (2) identify morphological and (3) chemical characteristics of chestnut related to resistance. To quantify the brown moth attack, experimental commercial genotypes were studied in three consecutive years (2014-16). The biometric characteristics of the nuts were evaluated, such as weight, length, width, distal thickness and thickness of the nut insertion with the pseudofruit. The chemical analysis of cashew liquid was performed in high performance liquid chromatography (HPLC), comparing the three most resistant genotypes with the most susceptible genotype. Regarding the biometric characteristics of the nuts, genotype MG 113 presented greater weight, length and width differing from the other genotypes. As for the distal thickness of the chestnut shell, the genotypes PRO 105/5 and PRO 112/8 were the thickest; while for the insertion thickness the genotypes MG 113, PRO 143/7, PRO 105/5, PRO 120/4, H 111/2 and PRO 112/8 presented the highest values. In the chemical analysis, in bored nuts, genotypes MG 170 and PRO 155/2 presented the highest content of anacardic acids, followed by genotype PRO 143/7. However, the genotypes PRO143 / 7, PRO 155/2 and MG 170, considered moderately resistant to A. phytomiella, showed higher levels of diene. The genotypes PRO 143/7, PRO 155/2 and MG 170 are moderately resistant, and the morphological characteristics that contribute most to the resistance of the dwarf cashew to the brown moth are the length, width and thickness of the chestnut insertion. In nuts, the content of anacardic acids was higher in the genotypes PRO 143/7, PRO 155/2 and MG 170, and in these genotypes the highest diene and monoene content was identified.